2016
DOI: 10.1007/s00259-016-3506-2
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of 18F-FDG PET/CT to predict tumour response and prognosis of patients with esophageal cancer treated by chemoradiotherapy

Abstract: Texture features IV and SZV, and volumetric parameters MTV and TLG can predict tumour response, but all of them have limited value in prediction of prognosis of patients with esophageal cancer treated by CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 35 publications
1
82
1
Order By: Relevance
“…Kaplan-Meier analysis (univariate analysis) was performed using thresholds established by ROC analysis in cases in which ROC showed statistical significant results. A multivariate Cox hazard analysis was conducted to determine independent prognostic parameters as well as relative risks (RR) [26,30]. Non-parametric logrank tests were used to assess the differences in the Kaplan-Meier curves; statistical significance was considered with a p value G 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan-Meier analysis (univariate analysis) was performed using thresholds established by ROC analysis in cases in which ROC showed statistical significant results. A multivariate Cox hazard analysis was conducted to determine independent prognostic parameters as well as relative risks (RR) [26,30]. Non-parametric logrank tests were used to assess the differences in the Kaplan-Meier curves; statistical significance was considered with a p value G 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…In case of multiorgan involvement, a maximum of three lesions per organ (largest in size and metabolically most active lesion) was segmented. A manual segmentation method was preferred in order to exclude adjacent physiological SSTR-avid structures on PET/CT images [26]. TF analysis was performed by using the Interview Fusion Workstation (Mediso Medical Imaging Systems Ltd., Budapest, Hungary) [13].…”
Section: Pet/ct Imaging Imaging Interpretationmentioning
confidence: 99%
“…Other more recent works explored the potential of texture analysis on PET images for the prediction of tumour response to CRT on patients with oesophageal cancer. Nakajo et al 87 found that intensity variability and size-zone variability were higher in patients who were non-responders than responders. Yip et al 37 studied the impact of different image registration methods for the definition of tumour volume after CRT on the estimation of several textural features.…”
Section: Application Of Texture Analysis In Radiotherapymentioning
confidence: 99%
“…Hence, not surprisingly, combined 18 F-FDG PET-based approaches (i.e., volumetric plus tumor texture assessment) for outcome prediction have also been investigated, e.g. in esophageal cancer [20].…”
Section: Introductionmentioning
confidence: 99%